A comparison of faecal examination, commercial ELISA kit, and indirect-ELISA methods in the diagnosis of sheep fasciolosis - Utuk, Armagan Erdem; Simsek, Sami; Koroglu, Ergun (Elsevier Science Bv, 2012)
The aim of this study was to compare the diagnosis of sheep fasciolosis by faecal examination, commercial ELISA kit, and home-made indirect ELISA method. For this purpose, a total of 265 sheep faecal samples were examined with the sedimentation method and 185 sheep serum samples were examined both with a commercial ELISA kit and a home-made indirect ELISA method. The prevalence of Fasciola hepatica eggs was 4.9%. The prevalence of anti-F. hepatica antibodies was 16.2% using the commercial ELISA kit and 15.6% using the home-made indirect ELISA method. It is concluded that although the faecal examination is the gold standard in the diagnosis of sheep fasciolosis, serological tests should not be ruled out, and particularly the home-made indirect ELISA method may be preferred, since it is less expensive than commercial kits and has similar reliability rates. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Fasciola hepatica; Commercial ELISA kit; Home-made indirect ELISA; Sheep